A simple respirogram-based approach for the management of effluent from an activated sludge system. (August 2018) - Li, Zhi-Hua; Zhu, Yuan-Mo; Yang, Cheng-Jian; Zhang, Tian-Yu; Yu, Han-Qing
Graphical abstract: Highlights: Index Res/t was proposed to describe effluent without any parameter calibration. Transformation from respirogram status to operational status was established. The respirogram-based effluent management method is simple and reliable. Abstract: Managing wastewater treatment plant (WWTP) based on respirometric analysis is a new and promising field. In this study, a multi-dimensional respirogram space was constructed, and an important index Res/t (ratio of in-situ respiration rate to maximum respiration rate) was derived as an alarm signal for the effluent quality control. A smaller Res/t value suggests better effluent. The critical R′es/t value used for determining whether the effluent meets the regulation depends on operational conditions, which were characterized by temperature and biomass ratio of heterotrophs to autotrophs. With given operational conditions, the critical R′es/t value can be calculated from the respirogram space and effluent conditions required by the discharge regulation, with no requirement for calibration of parameters or any additional measurements. Since it is simple, easy to use, and can be readily implemented online, this approach holds a great promise for applications.